Sarekat Rakyat Padang Panjang 1923-1926 - Sovia Nelisia; Siti Fatimah; Azmi Fitrisia (Science and Environmental Journal for Postgraduate, 2018)
This study examines the Sarekat Rakyat Padang Panjang 1923-1926. In conducting this research, the researchers try to analyze how the communist-leaning Sarekat Rakyat entered Padang Panjang, one of the most famous cities in Minangkabau to go to Islam and was the site of the first Islamic Modernization in West Sumatra. This research goes into historical research by following the method of historical research with steps 1 (1) Heurousics that is finding and gathering information obtained as a source of data, the source of data in the form of written data in the form of documents, archives, newspapers obtained from PDIKM Padang Panjang, Museum Aditiyawarman, and Padang State University Library. (2) Source criticism is carried out by testing the authenticity and validity of the data. (3) conduct analysis and interpretation of the data that has been obtained. The selected data is selected with studies that can be trusted truthfully. (4) Histiography is the presentation of the results of research. The results of the study indicate that in the 20th century, Padang Panjang had once developed communists with Marxist Islam. The entry of communists or the Sarekat Rakyat into Padang Panjang was spearheaded by the Sumatra Thawalib teacher namely Datuk Batuah and assisted by Djamaludin Tamin, Arif Fadillah and Nata Zainuddin. The social condition of the Padang Panjang community which was under pressure from the Dutch colonial government caused the communists to be easily accepted by the Padang Panjang community. In addition to disseminating communist ideas, the leaders of comunist often linked Islamic teachings against the kafir government. Interestingly communist leaders in Padang Panjang making Sumatra Thawalib the first Islamic modernist school in Minangkabau as the basis of their movement in spreading communist ideas.